2019
DOI: 10.1055/a-0929-6287
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Consumption of Red Meat, Compared to Soy or Non-Soy Legume, Has No Adverse Effect on Cardio-Metabolic Factors in Patients with Type 2 Diabetes

Abstract: Background Recently, it has been proposed that red meat consumption could enhance risk of diabetes and worsen lipid profile and glycemic status, in comparison with soy or non-soy legume, but the results of clinical trials are controversial. Objectives This study aimed to compare the effect of red meat, soy bean, and non-soy legume consumption on cardio-metabolic factors in patients with type 2 diabetes. Methods This was a randomized controlled clinical trial which included 75 patients with diabetes, aged 40–65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 44 publications
(56 reference statements)
0
27
0
Order By: Relevance
“…Dietary fibre intakes in intervention arms were in line with the adequate intake (AI) as per the Australian nutrient reference values (25 g for women, 30 g for men) [30,32,[34][35][36]39,44], with the exception of four study interventions, which were not [23,33,41]. Simpson et al [27] reported an extreme 96 g/day dietary fibre intake, which would not be sustainable among free-living individuals in the longer term.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Dietary fibre intakes in intervention arms were in line with the adequate intake (AI) as per the Australian nutrient reference values (25 g for women, 30 g for men) [30,32,[34][35][36]39,44], with the exception of four study interventions, which were not [23,33,41]. Simpson et al [27] reported an extreme 96 g/day dietary fibre intake, which would not be sustainable among free-living individuals in the longer term.…”
Section: Discussionmentioning
confidence: 79%
“…Two studies (T2DM n = 2) reported a statistically significant between-group effect on FBI in favour of the legume intervention [ 23 , 24 ]; however, one of these also reported a statistically significant between-group difference at baseline (p = 0.02) [ 23 ]. Three studies (T2DM n = 3) observed a statistically significant between-group reduction in HbA1c in favour of legume intervention, with reported reductions ranging from 0.10−0.50% [ 23 , 25 , 27 ], however, one study also reported a statistically significant between-group difference at baseline ( p = 0.04) [ 23 ]. One study, comprising of two comparisons (T2DM n = 1, T1DM n = 1), reported statistically significant between-group effects for 2-h PPG in favour of legume interventions; however, raw baseline data was not reported and therefore the absolute change is unknown [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 ). Sensitivity analysis revealed that independent removal of one trial in estimation of ES of HbA 1c reduced the heterogeneity significantly [ 77 ], and removal of two RCTs changed the interpretation from significant to non-significant when estimating the ES of HOMA-IR [ 5 , 85 ]. However, reduction in fasting blood insulin in T2DM adults was not significant ( n = 8 RCTs, ES – 1.18; 95% CI – 2.54, – 0.08; p > 0.05; I 2 = 63%).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unclear whether replacing red meat with legumes is associated with a reduced risk of hypertension [ 16 , 17 ]. In addition, the majority of previous studies were conducted among healthy individuals or participants with hyperlipidemia or hypertension, and few studies investigated the effect of legumes on blood pressure among participants with type 2 diabetes; these studies showed that an 8-week consumption of legumes, 4–6 servings per week, did not have a significant effect on blood pressure among type 2 diabetes patients or individuals at risk of type 2 diabetes [ 18 20 ]. The low consumption rate of legumes compared to the recommended amount [ 17 ], as well as the small sample size, and the short follow-up period prevented the possible beneficial effect of legumes on blood pressure in these populations [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%